Original paperDiagnostic accuracy of dual-source coronary computed tomography angiography in patients after bypass grafting - Kępka, Cezary; Opolski, Maksymilian; Kruk, Mariusz; Pręgowski, Jerzy; Kowalewska, Anna; Wilkowska, Paulina; Dzielińska, Zofia; Karcz, Maciej; Rużyłło, Witold; Demkow, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Aim: To determine the diagnostic accuracy of dual-source (DS) coronary computed tomography angiography (CCTA) with improved temporal resolution in a population of symptomatic patients after coronary artery bypass grafting (CABG) compared to invasive coronary angiography (ICA). Material and methods: Ninety (74 male, mean age: 68 ±9 years) symptomatic post-CABG patients from the prospective ANIN Coronary Computed Tomography Angiography Registry who underwent both DS-CCTA and ICA for suspected graft disease were included in the analysis. A total of 202 grafts (67 arterial grafts, 135 venous grafts) and 1,105 segments in 360 native coronary arteries  1.5 mm in diameter were evaluated for the presence of significant stenosis, defined as  50% decrease in vessel diameter. Results were compared with ICA as the standard of reference. Results : Sensitivity, specificity, and positive and negative predictive values of DS-CCTA for the detection of significant lesions in bypass grafts were 99%, 96%, 94%, and 99%, respectively. Segment-by-segment analysis of native coronary arteries for the detection of obstructive disease yielded sensitivity of 91% with specificity of 92%. If analysis was restricted to non-grafted and distal runoff segments, sensitivity and specificity were 88% and 96%, respectively. The presence of coronary calcium deposits was associated with a significant decrease in diagnostic accuracy of DS-CCTA. Conclusions : The DS-CCTA allows reliable evaluation of suspected graft disease in symptomatic post-CABG patients, whereas ICA is still required for the assessment of significant stenoses in native coronary circulation.